APOE ε4 allele drives female-specific Alzheimer’s disease progression via vascular dysfunction and tau spreading - Huang, Shuai; Wu, Jiawei; He, Ling (Frontiers in Neuroscience, 2025)
BackgroundApolipoprotein E (APOE) epsilon4 (ε4) is a major genetic risk factor for late-onset Alzheimer’s disease (AD), with women exhibiting heightened vulnerability to APOE ε4-associated cognitive impairment. Despite recognition of this sexual dimorphism, the underlying biological mechanisms remain incompletely understood.MethodsWe performed weighted gene co-expression network analysis (WGCNA) on RNA-seq data from the Mayo Clinic cohort (n = 277 temporal cortex samples) to identify sex- and APOE ε4-linked co-expression modules. 315 hub genes were identified within the most relevant gene modules derived from female AD patients with APOE ε4. The expression patterns of representative hub genes were then validated in female APOE ε4 carriers. Causal genes were prioritized via Summary-data-based Mendelian Randomization (SMR), and diagnostic biomarkers were identified using machine learning. Single-cell RNA-seq elucidated cell-type-specific gene expression, and Connectivity Map (CMap) screening nominated candidate therapeutics validated in a tauopathy mouse model (AAV-hTau-injected APP/PS1 mice).ResultsFour co-expression modules (tan, blue2, grey60, antiquewhite4) specifically correlated with female AD patients with APOE ε4-positive and were enriched for vascular endothelial development and extracellular matrix pathways. Ten hub genes were implicated in the pathogenesis of female-specific APOE ε4 AD. LAMC1, RBMS2, TMOD3, and LRP10 were suggested as key drivers of AD progression associated with endothelial dysfunction. Single-cell analysis confirmed endothelial-specific upregulation of these genes in female APOE ε4 AD brains. Drug repositioning nominated the vasodilator vincamine, which downregulated Lrp10, Lamc1 in cortex tissue, and effectively inhibited the tau protein propagation from the medial entorhinal cortex (MEC) to the hippocampus in female AD mice.Conclusionwe reveal a female-specific APOE ε4-driven molecular network linking endothelial dysfunction to tau pathology. These hub genes provide potential biomarkers, while vincamine represents a targeted prevention and therapeutic candidate for high-risk APOE ε4-positive women.